A Rare Case of Ruptured Giant Adrenal Myelolipoma Presenting with Spontaneous Intre-Abdominal Haemorrahage: A Case Report - Mbaba, Awajimijan Nathaniel; Abdalla, Khalid Mohamed; Ahmed, Hamza Mustapha; Ogolodom, Michael Promise (European Scientific Journal, ESJ, 2023)
Adrenal myelolipoma is a rare benign neoplasm of mesenchymal origin composed of mature fatty tissue and bone marrow elements. It is a non-functioning benign tumor, usually asymptomatic and commonly detected incidentally during evaluation for unrelated symptoms; hence, it is usually referred to as an “incidentaloma”. Large myelolipomas can cause mass effects and vague abdominal pain, spontaneous tumor rupture with massive hemorrhage is a more dramatic manifestation, though, it is an uncommon entity. We report the case of a 41-year-old anemic male patient who underwent an abdominal CT study and a huge hemorrhagic adrenal myelolipoma was detected to reiterate the importance of recognizing the characteristic radiological features of myelolipoma to accurately diagnose these tumors and emphasize the inclusion of myelolipoma in the lists of differential diagnosis of causes of spontaneous intra-abdominal hemorrhages.